Woody Species diversity and population structure along an Altitudinal gradient in Yegof Mountain Forest in North East of Ethiopia - Eyob Yimer; Tesfay Atsbha (Forest Science and Technology)
Environmental gradients (altitude) are the factors that determine the woody species diversity and population structure of a given forest. This study was conducted to determine the influence of altitude in the Yegof mountain forest’s woody species diversity and population structure within three altitudinal gradients: upper altitude (UP); lower altitude (LA) and middle altitude (MA). A total of 57 quadrats of 20 m by 20 m, 5 m by 5 m and 2 m by 2 m with nine horizontal transect lines were used for collecting the data on tree, shrub, and regenerating population, respectively. The vegetation data were analysed statically in one-way analysis of variance using R software. The study area, Yegof Mountain, showcases a rich diversity of plant species, revealing a total of 57 species across 49 genera and 37 families. These species are categorized into various growth forms, with 25 species (45%) identified as shrubs, 18 species (33%) as trees, 5 species (9%) as tree/shrubs, and 8 species (14%) as climbers. The composition of woody species varies significantly across different altitudinal gradients. In the LA gradient, 31 species were recorded, with 12 being unique; the MA gradient contained 37 species, also with 12 unique species; while the UA had 24 species, with only 7 unique. Elevation is a crucial factor influencing species diversity, as indicated by the Shannon diversity index values, which show UA having the highest diversity (3.03), while LA and MA presented lower but similar values (2.65 and 2.73, respectively). The combination of greater environmental heterogeneity, reduced competition and moderate disturbance at higher altitudes facilitates the coexistence of a greater number of species compared to lowland areas, and the regeneration status of a population gives a positive response as altitude increases. Thus, it is imperative to implement better ecological, policy, and socioeconomic measures in the area, particularly in LA, when compared to the other gradients.